Professional Development Opportunities as a determinant of Turnover Intention: A case of teachers in Public Secondary Schools in Meru County, Kenya - Ekabu, Peter (Technium Social Sciences Journal, 2020)
The study sought to establish whether the availability or non-availability of professional development opportunities determine the turnover intention of teachers in public secondary schools in Meru County, Kenya. Descriptive survey design, where both qualitative and quantitative paradigms were employed. The study population comprised of 2582 secondary school teachers and principals in 367 public secondary schools. Stratified proportionate sampling and simple random sampling methods were used to pick 518 participants who included 503 secondary school teachers and 15 secondary school principals. Questionnaires were used to collect quantitative data from teachers while interview schedules were used to collect qualitative data from the sampled principals. The hypothesis was tested using the Pearson Product-Moment Correlation and chi-square goodness of fit. Computer software SPSS Version 21 aided in data analysis. An analysis of the Pearson product-moment correlation showed a negative correlation between professional development opportunities and the turn-over intention of teachers in secondary schools in Meru County. Equally, Chi-square results corroborated indicating a strong and significant association of professional development opportunities and turn-over intention of teachers in secondary schools in Meru County. The study concluded that a lack of professional development opportunities leads to low morale, low motivation, and high turnover intention of teachers in public secondary schools in Meru County. The study recommended that the education stakeholders including the schools’ Boards of Management, the Ministry of Education, and the Teachers Service Commission among others motivate teachers by regularly offering them professional development. This would enhance their pedagogical skills thus reducing turnover intention among teachers.